Sustained Release of Phosphates From Hydrogel Nanoparticles Suppresses Bacterial Collagenase and Biofilm Formation in vitro - Nichols, Dylan; Pimentel, Marja B.; Borges, Fernando T. P.; Hyoju, Sanjiv K.; Teymour, Fouad; Hong, Seok Hoon; Zaborina, Olga Y.; Alverdy, John C.; Papavasiliou, Georgia (Frontiers in Bioengineering and Biotechnology, 2019)
The intestinal tract undergoes various injuries due to disease and/or surgical interventions. The presence of pathogens at injured sites contributes to healing impairment. Members of the intestinal microbiome often express increased collagenase levels due to injury or disease, a key phenotype leading to collagen degradation and healing complications. Antibiotic administration is often ineffective for addressing these issues as it inadvertently eliminates members of the normal flora, allowing pathogenic bacteria to “bloom” and acquire antibiotic resistance. The use of non-antibiotic compounds to attenuate collagenase production while allowing commensal bacteria to proliferate normally offers key advantages including suppression of pathogenic phenotypes and reduction of emergence of resistance. We have previously shown that intestinal phosphate depletion in the surgically stressed host is a major cue that triggers bacterial virulence, whose expression is suppressed under phosphate abundant conditions. Systemic administration of phosphate, however, is susceptible to rapid clearance. To address this barrier, we present a drug delivery approach for sustained release of phosphates from polyphosphate (PPi)-loaded poly(ethylene) glycol (PEG) hydrogel nanoparticles (NP-PPi) as a means of providing an intestinal phosphate rich environment for attenuation of collagenase. The efficacy of NP-PPi in mitigating collagenase and biofilm production of pathogens (P. aeruginosa, S. marcescens and E. faecalis) expressing high collagenolytic activity was investigated in vitro. Treatment with NP-PPi significantly reduced (> 90%) collagenase and biofilm production of gram-negative S. marcescens and P. aeruginosa as compared to the no treatment control. In the case of gram-positive E. faecalis, the efficacy of treatment with NP-PPi was found to be less prominent for collagenase (~ 20%) and biofilm attenuation as compared to the no treatment control. Given the efficacy of monophosphate (Pi)-loaded NPs (NP-Pi) in suppressing collagenase of E. faecalis, we investigated a combination treatment of NP-Pi and NP-PPi and confirmed its utility in attenuating E. faecalis collagenase levels (38% reduction as compared to the no treatment control). These findings suggest that a combination therapy of NP-PPi and NP-Pi confers protection against gram-positive and gram-negative collagenolytic strains thereby providing a promising therapeutic strategy to suppress tissue-disruptive bacterial phenotypic expression without eradicating protective flora over the course of intestinal healing.